CORRELATION AND PATH ANALYSIS IN COWPEA (Vigna unguiculata (L.) Walp) - RM. NAGALAKSHMI; R. USHA KUMARI; R. ANANDA KUMAR (The Bioscan, 2020)
Knowledge on the relationship between yield and yield related characters is essential for designing any plant breeding programme. With this aim, a study was conducted in cowpea (Vigna unguiculata (L.) Walp) to estimate the correlation coefficients among 12 quantitative characters and to analyse the direct and indirect effects of these characters on seed yield by path coefficient analysis in 66 genotypes collected from various agroclimaic zones of India. The study revealed that seed yield was positively and significantly correlated with number of pods per plant (0.40), peduncle length (0.38), number of clusters per plant (0.31), number of seeds per pod (0.29), number of leaves per plant (0.28), number of branches per plant (0.27) and days to 50% flowering (0.19). 100 seed weigh (-0.44) and pod length (-0.1) were negatively correlated with seed yield. Number of seeds per pod (0.34), peduncle length (0.26), plant height (0.23), number of branches per plant (0.15), number of clusters per plant (0.12), number of pods per plant (0.12) and days to 50% flowering (0.07) exerted a direct positive association with seed yield. The results of correlation and path analysis suggests that seeds per pod, pod length and number of branches per plant are the important characters for selection in cowpea.